Análise da qualidade microbiológica em leite pasteurizado, tipo C, recém pasteurizado e na data de validade - Oliveira, Débora Cristina Vidal de [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The conservation of raw milk for long periods of time under refrigeration can result in the lost of its quality. This happens because bacterias, capable of developing in low temperatures, as psichrotrophics, in milk, associates with its enzymatic activities, are capable to degradate it. Although the pasteurization of milk sufficiently diminishes the transmission of the illnesses, that generally eliminates such microorganisms, is not a total efficient process because many enzymes produced for such bacterias are termostable, being able to resist the treatment and to remain active, leading to the loss of the quality of milk and its derivatives. The Normative Instruction 51 of 2002 established that milk must be cooled and stored in the production property, what resulted increasing the incidence of such bacteria in population destined milk. In some parts of the world contaminated milk is causing serious risks to the health of the population, assuming great importance in Public Health, mainly in relation to the hygienic-sanitary conditions of the product. ANVISA establishes, thus, maximum bacteriological concentration that must be evidenced before commercializing the product, guaranteeing the quality of milk as proper for consumption. Based on these aspects, the objective of this work is the microbiological analysis of 30 milk samples type C, collected in bakeries of the city Botucatu, in the state of São Paulo. Analysis were made to determinate the most likely number of termotolerants coliforms, as well the number of colony units of psichrotrophics bacterias, the presence of Salmonella and the enumeration of positive Staphylococcus aureus, at the moment of purchase and validity of the products

A conservação do leite cru por longos períodos de tempo sob refrigeração pode levar a perda de sua qualidade. Isso se deve ao fato de que bactérias psicrotróficas, capazes de se desenvolverem em baixas temperaturas, secretam enzimas lipolíticas e proteolíticas, que degradam o leite. Embora a pasteurização do leite diminua bastante a transmissão das doenças, uma vez que geralmente elimina tais microorganismos, não é um processo totalmente eficaz quanto à deterioração, uma vez que muitas enzimas produzidas são termoestáveis, podendo resistir ao tratamento, permanecendo ativas, causando a perda de qualidade do leite e de seus derivados. Em várias partes do mundo, o leite contaminado vem causando sérios riscos à saúde da população, assumindo grande importância em Saúde Pública, principalmente em relação ao controle higiênico-sanitário do produto. Com base nesses aspectos, o trabalho teve como objetivo a análise microbiológica de 30 amostras de leite tipo C, recém pasteurizados, comercializados em padarias e supermercados da cidade de Botucatu, SP e a análise de uma amostra do mesmo lote de leite, mas na data limite de validade, totalizando 60 amostras. Foi realizada a determinação do número mais provável de coliformes termotolerantes, enumeração de Staphylococcus aureus e de bactérias psicrotróficas e a pesquisa da presença de Salmonella, no momento de compra e validade dos produtos
Keywords: Microbiologia de alimentos; Leite